Ocenka skorostno-silovych vozmožnostej lyžnikov-gonšcikov v polevom testirovanii - Reutskaya, E. A.; Pinyagin, P. Yu. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
For the successful training process in cross-country skiing, monitoring the physical fitness of athletes is required. In order to effectively assess the speed and power capabilities of skiers in real conditions, a test `skiing 100 m double-polling` was proposed. The simplicity of the test allows it to be used in the practice of skiing coaches for the stage controlling of speed-strength capabilities of skiers. Check of the test for the informativeness and reliability showed that proposed test meets the necessary conditions.